1989
DOI: 10.1063/1.456765
|View full text |Cite
|
Sign up to set email alerts
|

Propargylene: A C3H2 isomer with unusual bonding

Abstract: Propargylene was identified in a matrix as a product of photolysis of cyclopropenylidene and diazopropyne. The molecule is a triplet. The optimum geometry predicted by ab initio calculations corresponds to a structure HC≡C–C̈H. The transition structure in the interconversion HC≡C–C̈H⇄HĊ=C=ĊH⇄HC̈–C≡CH is very low in energy and close to the energy of the vibrational ground state. Owing to this nonrigidity, computed infrared (IR) frequencies based on a harmonic treatment do not match the experimental spectrum. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 14 publications
5
50
0
Order By: Relevance
“…Ever since three cumulene carbenes (where, n = 3, 4, and 6) were identified in space [16][17][18] followed by their detection in the laboratory, 27,[37][38][39] both experimentalists and theoreticians have started focusing their attention not only on these compounds but also on their isomers and higher homologous series. [40][41][42][43][48][49][50][51][52][53][54][55][56][57] Although more than hundreds of structural isomers are theoretically possible for C 7 H 2 , 58 to date merely six isomers (see Fig. 1 and 2) have been detected experimentally 43,59,[60][61][62][63] and none have been detected in space.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since three cumulene carbenes (where, n = 3, 4, and 6) were identified in space [16][17][18] followed by their detection in the laboratory, 27,[37][38][39] both experimentalists and theoreticians have started focusing their attention not only on these compounds but also on their isomers and higher homologous series. [40][41][42][43][48][49][50][51][52][53][54][55][56][57] Although more than hundreds of structural isomers are theoretically possible for C 7 H 2 , 58 to date merely six isomers (see Fig. 1 and 2) have been detected experimentally 43,59,[60][61][62][63] and none have been detected in space.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] We are unaware of any previous assignments for the ν 4 mode (or, for that matter, any gas-phase vibrational assignments for H 2 CCC), but are confident in our conclusion that ν 4 = 1111 ±11 cm −1 . The assignments above are supported by the Franck-Condon simulation (see Fig.…”
mentioning
confidence: 95%
“…9 Propadienylidene (H 2 CCC) was first generated and characterized in an argon matrix by Maier and co-workers. 10,11 Following the laboratory detection of H 2 CCC in the gas phase via millimeterwave spectroscopy, 12 this polar singlet C 3 H 2 carbene was soon discovered in two different astronomical sources, TMC-1 and IRC+10 216. 13 Subsequent millimeter-wave and Fourier transform microwave spectroscopy studies yielded rotational constants for the ground state of H 2 CCC (Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Moreover, all of them can be interconverted by photolysis. [17][18][19] The structural characters, thermochemistry, and isomerization of C 3 H 2 carbenes have been investigated extensively. 13,18,[20][21][22] It was found that the singlet cyclopropenylidene is the most stable isomer among the three species, [23][24][25][26] which is lower in energy by about 42-59 and 59-92 kJ/mol than that of propadienylidene and propynylidene, respectively.…”
Section: 12mentioning
confidence: 99%